Spatial-temporal Pattern and Influencing Factors of Listed Enterprises in China’s Strategic Emerging Industries - Peichao Dai (Universitas Atma Jaya Yogyakarta, 2025)
This study analyzes the structure and spatial distribution of listed companies in China's strategic emerging industries (SEIs) from 2010 to 2021, using a quantitative approach. An industrial diversity index is created to assess provincial structures, and spatial agglomeration is examined through a spatial autocorrelation model. The distribution is visualized with kernel density estimation (KDE), and migration patterns of the gravity center are tracked. The key findings are as follows: (1) Significant regional disparities in SEI development exist, with greater diversity in the Yangtze River Delta (YRD), Beijing-Tianjin-Hebei (BTH), and the Pearl River Delta (PRD) compared to other regions; (2) The distribution shows strong positive spatial autocorrelation, indicating a pronounced agglomeration effect; (3) The spatial center of gravity primarily shifts within Central China; (4) The distribution follows a pattern of decreasing concentration from the eastern coastal areas to the western inland regions, with scattered presence in the central and northeastern regions; (5) Key factors such as economic development (DN values), policy support, R&D investments, passenger turnover, and technology market activity play a significant role in shaping the number of listed companies in each region. This analysis offers valuable insights for policymakers aiming to guide regional industrial development.